2014
DOI: 10.1002/cncr.28679
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of adjuvant chemotherapy in patients with resected non‐small cell lung cancer

Abstract: BACKGROUND Despite clinical trials demonstrating improved survival with adjuvant chemotherapy (AC) for patients with American Joint Committee on Cancer stages I to III non‐small cell lung cancer (NSCLC), it is unclear whether this survival benefit extends to broader populations. The current study evaluated patterns of AC use and examined the impact of AC on survival. METHODS A retrospective analysis was conducted of patients in the Veterans Affairs Central Cancer Registry diagnosed with stages IB to IIIA NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…1 Doublet chemotherapy (vinorelbine plus cisplatin [VP]) is a standard adjuvant treatment for resected stage II-III NSCLC. [2][3][4] Radiation therapy has a role before or after surgery for N2 patients. 5,6 Evidence of the clinical benefits of adjuvant chemotherapy for resected early-stage NSCLC has been shown in a meta-analysis demonstrating that 5-year survival rates increased by 4%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Doublet chemotherapy (vinorelbine plus cisplatin [VP]) is a standard adjuvant treatment for resected stage II-III NSCLC. [2][3][4] Radiation therapy has a role before or after surgery for N2 patients. 5,6 Evidence of the clinical benefits of adjuvant chemotherapy for resected early-stage NSCLC has been shown in a meta-analysis demonstrating that 5-year survival rates increased by 4%.…”
Section: Introductionmentioning
confidence: 99%
“…16 Similarly, in a database analysis of patients treated within the Veterans Affairs (VA) system, the use of adjuvant chemotherapy was associated with an 18% decreased risk of death after surgical resection in patients with stages IB to IIIA NSCLC. 17 With a median age at diagnosis of 70 years, NSCLC results in a significant disease burden among the elderly. 18 To the best of our knowledge, there are no prospective trials of adjuvant chemotherapy limited to older patients published to date.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of NSCLC is complex, and decisions regarding the administration of adjuvant therapy for stage IB NSCLC patients remains controversial. Some research studies have suggested that patients with stage IB NSCLC could benefit from adjuvant therapy (16)(17)(18), while other studies have reported no effects of adjuvant chemotherapy on patients (9,11,12,(19)(20)(21). Studies that have shown the benefit of adjuvant chemotherapy in stage IB patients tend to recommend adjuvant therapy for patients with tumor size ≥4 cm (7,8,12,22,23).…”
Section: Discussionmentioning
confidence: 99%